Rusties and Riddles and Gee-Haw Whimmy-Diddles - Still, James (Book collections on Project MUSE., 2015)
The people of the Kentucky mountains and the southern Appalachians preserved a language alive with colorful turns of phrase and whimsical wit and for their amusement they created a rich vein of oral lore -- songs, tales, and games. James Still presents a varied and entertaining collection of riddles, whimsies, and verbal pranks, gathered through his long association with the mountain people of eastern Kentucky. This book includes in one volume two earlier books -- Way Down Yonder on Troublesome Creek and The Wolfpen Rusties -- that have been unavailable for several years. It contains the com.